Estrategias de motivación para abordar la atención dispersa en estudiantes del cuarto grado “B”, Escuela de Educación Básica “Miguel Riofrío” Loja, periodo 2023 – 2024 - Barrionuevo Diaz, Heidy Jamileth (2024)
The present research includes a study on motivation strategies to address dispersed attention in students. For this purpose, the general objective is: To determine the influence of motivation strategies on the learning of the subject of Mathematics in fourth grade “B” students, afternoon section, of the “Miguel Riofrio” School, Loja city, period 2022 – 2023. Its purpose was to describe and explore the causes and factors that contribute to dispersed attention, to design and propose motivation strategies based on research and evaluate the effectiveness of the proposed strategies. The study area of the project was the “Miguel Riofrío” School of Basic Education. The research had a mixed approach, since the strengths of qualitative and quantitative methodology were taken, the design is quasi-experimental since a Pre-test and a Post-test were applied. The methods used for the collection and analysis of information were: Scientific, descriptive, analytical, synthetic, hermeneutical method. The technique that was used to understand the problem was direct observation with which it was distinguished that the children did not have a good motivation to attend classes. The instruments that were used to collect the information were: a survey directed to the teachers, to know what strategies they use to achieve the students' attention, and an attention deficit disorder test on a sample of 18 students, which allowed us to know the current state of the problem. A difference was determined between the pre and post - test, positively influencing the application of motivation strategies to counteract dispersed attention, so that teachers are recommended to use the guide to improve attention in the classroom.